Evaluation of Liner Cavitation Potential through Piston Slap and BEM Acoustics Coupled Analysis - Xiaoyu Wang; Haofeng Wang; Jingchao Zhao; Shenghao Zhou; Zhong Luo; Qingkai Han (Mathematics, 2022)
Internal combustion engines take up the major position in the power facility market and still encounter some challenges; one key issue is liner cavitation erosion. The impact vibration between piston and cylinder generates pressure fluctuation on the wet liner surface and leads to the occurrence of cavitation in the case that coolant pressure falls below its vapor pressure. Piston slap methodology has been improved by considering the dynamic characteristics of the piston. Water coolant passage acoustic features were investigated and the Helmholtz effect between cylinders was confirmed. In order to address the cavitation erosion potential of the engine cylinder, acoustic pressure in the cooling water passage was investigated by boundary element method analysis with the acceleration of the cylinder liner which was obtained from the piston slap program. This study revealed that a certain acoustic mode of the cooling water passage had a dominant effect on the amplitude of water coolant dynamic pressure induced by liner vibration. Measures of eliminating the acoustic mode are believed to be able to suspend pressure fluctuation and furthermore the potential of cavitation.